The Principal's Strategy in Enhancing Teacher Professionalism at Al-Husna Islamic Boarding School Private High School - Dosma Gabena Harahap; Syaiful Bahri; Salim Aktar (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to analyze the strategies implemented by the principal to enhance teacher professionalism, examine the implementation of these strategies, and identify the challenges faced during the process at Private High School Pesantren Al-Husna Marindal 1. Methodology: A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The research focused on the strategic efforts of the school principal in developing the professional capacity of educators. Main Findings: The findings indicate that the school principal has implemented relatively effective strategies to improve teacher professionalism. However, significant challenges were identified, including limited transportation facilities for teachers and suboptimal execution of academic supervision. These factors substantially affect the quality of the strategy's implementation. Novelty/Originality of this study: This study highlights the specific challenges in enhancing teacher professionalism within the unique context of pesantren-based schools, offering critical insights for stakeholders to design systematic interventions that address these barriers and support professional capacity development in similar educational settings.